2008
DOI: 10.1108/13620430810849506
|View full text |Cite
|
Sign up to set email alerts
|

The construct validity of Schein's career anchors orientation inventory

Abstract: The purpose of this paper is to test the construct validity of the measurement model of Schein's Career Orientation Inventory (1990) where entrepreneurship and creativity constitute two separate constructs. Design A fairly representative sample of 1,847 Israeli working adults completed Schein's Career Anchor Inventory (COI) questionnaire. The data was subjected to confirmatory factor analysis to compare the fit of the proposed nine-construct model to Schein's eight Findings The findings demonstrate that a) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 16 publications
6
54
2
3
Order By: Relevance
“…For a technician, specialization is motivated by security, whereas for a professional, expertise meets a need for professional growth. Second, our results corroborate the conclusion of Danziger, Rachman-Moore and Valency (2008) that the entrepreneurial creativity anchor also needs to be reformulated. The concept of creativity is distinct from that of entrepreneurship.…”
Section: Validation Of the Career Value Structure Modelsupporting
confidence: 81%
See 1 more Smart Citation
“…For a technician, specialization is motivated by security, whereas for a professional, expertise meets a need for professional growth. Second, our results corroborate the conclusion of Danziger, Rachman-Moore and Valency (2008) that the entrepreneurial creativity anchor also needs to be reformulated. The concept of creativity is distinct from that of entrepreneurship.…”
Section: Validation Of the Career Value Structure Modelsupporting
confidence: 81%
“…Empirical studies show that the security/stability anchor has been split into two factors, organizational security (good employee benefits, advantageous pension plan) and geographical security (job stability in a given place) (DeLong, 1982a(DeLong, , 1984Jiang, Klein and Balloun, 2001). The entrepreneurial creativity anchor has also been divided into two (Danziger, Rachman-Moore and Valency, 2008). Additionally, the debate centers on specific anchors.…”
Section: Facts and Career Anchor Theorymentioning
confidence: 99%
“…In fact, significant differences between women and men's CAs were found, with two exceptions: technical/functional competence and security. These results do not provide evidence of the generalizations of Danziger's et al (2008) results in so-called Western societies. Similar discussions were addressed in studies conducted in developing countries.…”
Section: Introductioncontrasting
confidence: 42%
“…Similarly, for Schein's (1975) Career Orientation Inventory it was found that businessrelated entrepreneurship (business talent) and creativity constitute two separate constructs. Danziger et al (2008) test the construct validity of the two-factor model with 1,847 Israeli working adults and provide strong support for the distinction between these two dimensions. In accordance with this literature, we factorize the entrepreneurial selfefficacy items without the creativity items (coded 'C' in Appendix C) and find that there is only one factor with an eigenvalue exceeding 1.…”
Section: Page 11 Of 34mentioning
confidence: 99%
“…There are many studies on entrepreneurial self-efficacy, but to the best of our knowledge there is only one study that distinguishes psychometrically between entrepreneurial creativity and entrepreneurial business talent. Based on a survey of 1,847 Israeli working adults, Danziger et al (2008) report that the 'entrepreneurial creativity' dimension within Schein's (1975) career orientation inventory needs to be split into two factors: entrepreneurship and creativity. These results, along with our own findings, clearly demonstrate that more research is needed to improve the rather rudimentary measurement of creativity vis-à-vis other business-related talents.…”
Section: Limitations and Future Researchmentioning
confidence: 99%